O dano ambiental extrapatrimonial coletivo e o risco: um novo enfoque - Jardim, Luciana Chiavoloni de Andrade (2016)
This paper consists in the development of collective extra patrimonial environmental damage analysis due to the risk in contemporary society. The goal is the enforcement of the environmental protection in its wide conception, stablishing assumptions to application of liability for collective extra patrimonial environmental damage. Thus, this study – which using deductive method and bibliographical research – discusses about conceptualization of the damage under civil perspective. It adresses the environmental legal protection, considering environmental meaning and its relation with dignity of human person, and the characterization of material good and pollution, to support liability for collective extra patrimonial environmental damage. We considered sensitive issues such as causal link, tolerability and detrimental complexity of environmental damages, according to cross border effects and intergenerational interests affected. We also related collective extra patrimonial environmental damage with prevention and precaution principles. At the conclusion, we propose a new classification for damage, the damage-damage and the damage-risk, to demonstrate that risk (concret or abstract) is not configured as future damage or as liability without damage, but rather damage itself, giving rise to application of liability for collective extra patrimonial environmental damage